(3cTa GdQjH aj GdYed HGdLjHs - (3eMeO Hf CMeO Hf YHO GdQMje GdeRj GdeGdcj , TeS GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdeRi GdMeO ddg QH GdYGdejf hHYO aEfg djS ai GdGdGJ GdadcjI eG jYed Hg LejY GdGYeGd s
(3BNQgG (B:s
(3adh GSJYedJ NeSgG hNeSg Gh YTQgG hYTQI jNQL dc eG JQjO hbO GfaJM GdHGH dg def dg GOfi JCed hage adjcf GNQgPG GdcdGe JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1490s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs